Non-pharmacological therapies for treating non-motor symptoms in patients with Parkinson’s disease: a systematic review and meta-analysis - Zhang, Yu; Liu, Shuang; Xu, Ke; Zhou, Yan; Shen, Yiwei; Liu, Zhengnan; Bai, Yan; Wang, Shun (Frontiers in Aging Neuroscience, 2024)
The non-motor symptoms of Parkinson's disease (PD) are an important part of PD.In recent years, more and more non-drug interventions have been applied to alleviate the non-motor symptoms of PD, but the relevant evidence is limited.This systematic review and meta-analysis was designed to evaluate the efficacy of non-drug interventions in patients with non-motor symptoms in patients with PD. Methods: Seven databases, including Pubmed, Embease, Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang database (WANFANG), VIP database(VIP), and China Biomedical Literature Service System (CBM) were searched from the establishment of the database to December 2023. Non-drug interventions such as acupuncture, cognitive behavioral therapy (CBT), exercise, repetitive transcranial magnetic stimulation (rTMS), and non-motor symptoms of Parkinson's disease were selected as search words, and two independent evaluators evaluated the included literature's bias risk and data extraction. The therapeutic efficacy was evaluated by the Parkinson's Disease Sleep Scale(PDSS),Hamilton Depression Scale (HAMD), Beck Depression Inventory (BDI),Hamilton Anxiety Scale(HAMA), Montreal Cognitive Assessment (MoCA) , Minimum Mental State Examinatio(MMSE) , and Parkinson's Disease Questionnaire-39 (PDQ-39). RevMan 5.4.1 (Reviewer Manager Software 5.4.1). Cochrane Collaboration, Oxford, UK)analyzed the data and estimated the average effect and the 95% confidence interval (CI). A heterogeneity test is used to assess differences in the efficacy of different non-drug treatments.We selected 36 from 4027 articles to participate in this meta-analysis, involving 2158 participants. Our combined results show that: